Social Sensemaking with AI: Designing an Open-ended AI experience with a Blind Child - Morrison, Cecily; Cutrell, Ed; Grayson, Martin; Thieme, Anja; Taylor, Alex S; Roumen, Geert; Longden, Camilla; Faia Marques, Rita; Sellen, Abigail; Tschiatschek, Sebastian (The CHI Conference on Human Factors in Computing Systems, 2021)
AI technologies are often used to aid people in performing discrete tasks with well-defined goals (e.g., recognising faces in images). Emerging technologies that provide continuous, real-time information enable more open-ended AI experiences. In partnership with a blind child, we explore the challenges and opportunities of designing human-AI interaction for a system intended to support social sensemaking. Adopting a research-through-design perspective, we reflect upon working with the uncertain capabilities of AI systems in the design of this experience. We contribute: (i) a concrete example of an open-ended AI system that enabled a blind child to extend his own capabilities; (ii) an illustration of the delta between imagined and actual use, highlighting how capabilities derive from the human-AI interaction and not the AI system alone; and (iii) a discussion of design choices to craft an ongoing human-AI interaction that addresses the challenge of uncertain outputs of AI systems.